2014
DOI: 10.1002/mds.26005
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction and hyperhomocysteinemia in Parkinson's disease: Flow-mediated dilation study

Abstract: Our findings indicate that endothelial dysfunction may be associated with chronic l-dopa treatment in patients with PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 30 publications
(31 reference statements)
1
8
0
Order By: Relevance
“…Our study is the first that used peripheral arterial tonometry (PAT). Our results are consistent with FMD studies, showing lower RHI in PD subjects compared to controls [11,12].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study is the first that used peripheral arterial tonometry (PAT). Our results are consistent with FMD studies, showing lower RHI in PD subjects compared to controls [11,12].…”
Section: Discussionsupporting
confidence: 93%
“…l -dopa therapy exhibits increased levels of homocysteine that is considered a modest independent risk factor for vascular disease, causing endothelial damage and atherogenesis [ 15 , 24 ]. Yoon et al concluded that EF, as assessed by the FMD, may be associated with chronic l -dopa treatment in patients with PD [ 11 ]. Our results suggest no significant association between RHI and l -dopa treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding PD, a decreased FMD was found in patients treated with L-dopa compared to patients treated with L-dopa and entacapone, untreated patients, and control subjects. An inverse relationship has been demonstrated between FMD and hyperhomocysteinemia, which could explain the FMD reduction observed in the L-dopa group (Yoon et al, 2014). Overall, limited and conflicting evidences are available so far, mainly due to the advanced age and reduced cooperation of the patients.…”
Section: Identifying and Targeting Vascular Dysfunction In Neurodegen...mentioning
confidence: 99%
“…Endothelial dysfunction in PD may result from chronic L‐DOPA treatments (Yoon et al . ) and even acute administration increases regional cerebral blood flow and BBB permeability (Ohlin et al . ).…”
Section: Endothelial Activation and Dysfunction In Brain Disordersmentioning
confidence: 99%